Targeted versus chrono-targeted chemotherapy for inhaled chemotherapy in non-small cell lung cancer - Zarogoulidis, Paul; Darwiche, Kaid; Kalamaras, George; Huang, Haidong; Hohenforst-Schmidt, Wolfgang; Zarogoulidis, Konstantinos (Translational Lung Cancer Research, 2013)
Lung cancer long term survival still remains poor and early detection is still the best methodology to treatment. Therefore several novel approaches have been investigated for anticancer drug administration. Inhaled therapies for lung diseases are used since the ancient times. Inhaled anticancer treatment administration was firstly investigated almost 30 years ago. Since then the inclusion and exclusion criteria have been investigated in correlation with the safety and efficacy of cisplatin, 5-fluoracil, carboplatin, paclitaxel, docetaxel, 9-nitro camptothecine, gemcitabine, cetuximab, granulocyte-colony stimulating factor, interleukins and recently with bevasizumab. Along with the anticancer drug formulations administered, other aspects of this local treatment have been also investigated to improve the efficiency and safety, such as; proper nebulization system, drug formulation delivery system, setting of administration, aerosol protection measures, inhalation techniques and safety issues follow up. During the last years with the use of actigraphy wrist watches, an extended investigation of the circadian rhythm of animals and humans has been performed and new insights are included in lung cancer chemotherapy administration. The “personalized” therapy administration should not be considered only as a molecular pathway inhibition, but also as a chrono-targeted anticancer treatment.